Nilai Ekonomi Total Hutan Kayu Putih: Kasus di Desa Piru, Kabupaten Seram Bagian Barat, Provinsi Maluku - Parera, Evelin; Darusman, Dudung; Simangunsong, Bintang (Institut Pertanian Bogor (IPB University), 2006)
An undervaluation of melaleuca forest (MF) needs to be adressed since it affects a management of MF. Type of goods and services produced by MF were indentified. Their values were assessed using Forest Valuation tehniques such as market price and replacement cost methods and then used to determine the value of MF using total economic value (TEV) approach. The result showed that TEV of MF was aboutRp.1,6 million/ha/year (forest flow value). Water had the highest value ofRp.1,04 million/ha/year (or 66% of TEV) followed by leafs ofRp.0,4 million/ha/year(or 24% of TEV). The rest comprised of water, flora and fauna valueswas ofRp. 0,03 million/ha/year (or 1,6% of TEV). The value of MF was estimated about Rp.36 million/hectare (forest stock value).